Ho Chi Minh’s political culture - Nguyễn Tùng Lâm (Tạp chí Nghiên cứu Khoa học Công đoàn, 2023)
In the article, the author has presented basic characteristics of Ho Chi Minh’s political culture. Ho Chi Minh’s political culture is about the beauty, the beauty, and the sustainable values of his revolutionary activities towards the cause of national liberation, class liberation and human liberation. . In the revolutionary period in our country today, studying the views on Ho Chi Minh’s political culture on the above issue has great theoretical and practical significance, for the cause of national construction and defense. Socialist Vietnam.